African Regional and Inter-Regional Health Governance: Early Responses to the Covid-19 Pandemic by ECOWAS and the African Union. Issue 4 (2nd October 2021) - Engel, Ulf; Herpolsheimer, Jens
ABSTRACT: The Covid-19 pandemic brings back to the fore traditions of interconnected health governance in Africa, both at regional and inter-regional levels. Using the early pandemic responses of ECOWAS and the African Union as empirical case studies, we reconstruct (1) how already established regional actors in managing pandemics, such as the West African Health Organization (WAHO), are (2) now interacting with a newly established continental institution, the Africa Centers for Disease Control and Prevention (Africa CDC), established in response to the Ebola epidemic in West Africa (2014–2016). This is bolstered by policy responses coordinated by the African Union Chairperson and (3) forms of inter-regional pandemic governance that are being developed between ECOWAS and the African Union. Against this backdrop, we briefly develop a more conceptual argument on the relevance and nature of inter-regional cooperation between the African Union and ECOWAS. First, when compared to other world regions, interlocking forms of regionalism have allowed many African governments to respond to Covid-19 early on. In view of poorly equipped national health systems, and an array of other demanding challenges, early responses have at least bought affected states time to prepare national health systems, start mutual learning and organize international assistance – despite all shortcomings that still exist. Second, regional crisis response has been an opportunity to (re)negotiate the division of labor between the African Union and ECOWAS, which has been already ongoing in the area of governance, peace and security.